Weight Loss During Topiramate Treatment in a Severely Obese Adolescent with Congenital Adrenal Hyperplasia and Migraine - Amy Seagroves; Heather M. Ross; Alaina P. Vidmar; Mitchell E. Geffner; William S. Kim; Darryl Hwang; Claudia Borzutzky; Nicole R. Fraga; Mimi S. Kim (Galenos Yayincilik, 2023)
Youth with classical congenital adrenal hyperplasia (CAH) due to 21-hydroxylase deficiency exhibit an increased prevalence of obesity, early adiposity rebound, and increased abdominal adiposity compared to unaffected youth. Current obesity management in CAH largely focuses on lifestyle modifications. There is evidence that topiramate therapy is effective in reducing body mass index (BMI), as well as visceral adipose tissue (VAT), in unaffected adolescents with exogenous obesity. However, little is known about the efficacy of topiramate in patients with classical CAH. We report on a 17-year-old female with severe obesity and salt-wasting CAH due to 21-hydroxylase deficiency, who demonstrated reductions in BMI, as well as abdominal visceral and subcutaneous adipose tissue (SAT) while on topiramate therapy. The patient was diagnosed with classical CAH as a newborn with a 17-hydroxyprogesterone 11,000 ng/dL. She had a BMI over the 95th percentile at 3 years of age, followed by unremitting obesity. At 17 years old, she was started on topiramate to treat chronic migraines. Following three years of topiramate therapy, her BMI z-score decreased from +2.6 to +2.1. After four years of therapy, her waist circumference decreased from 110 to 101 cm, abdominal VAT decreased substantially by 34.2%, and abdominal SAT decreased by 25.6%. Topiramate therapy was associated with effective weight loss and reduced central adiposity in an adolescent with classical CAH and severe obesity, without any side effects. Further study is warranted regarding topiramate therapy in obese youth with classical CAH and increased central adiposity, who are at higher risk for significant morbidity.